Einfluss der periodischen Struktur auf geführte Wellen in gewebeverstärkten Polymeren - Claes, Leander (Fortschritte der Akustik - DAGA 2024)

Métodos de la mediación de cultura en el entrenamiento práctico de futuros/as profesores/as de Alemán como Lengua Extranjera - Treder, Alexandra (Revista Lengua y Cultura)
This study investigates the teaching methods that future teachers of German as a foreign language use in cultural mediation. Utilizing a qualitative and hermeneutic approach, it analyzes data from a teacher-training module of the International Master's in German as a Foreign/Second Language that Friedrich Schiller University Jena in Germany offers. Participants taught an online course to students from a Japanese university, which focused on cultural learning. Within the teacher training module, the participants discussed their lesson plans, conducted classes, and subsequently reflected on their teaching practices by exploring and critiquing the practical application of their teaching skills. The analysis, which was conducted using qualitative evaluative content analysis following Kuckartz's (2018) approach, revealed a preference for distributive/instructive methods, with some recognition of interactive and collaborative methods. A tendency towards both repetitive and reflective practices was evident, with a predominant focus on content that was specific to a supposed target culture rather than intercultural or transcultural content. The study highlights the need to balance knowledge transmission with the development of critical and reflective skills in cultural mediation. It emphasizes the importance of incorporating collaborative and interactive methods, which promote a critical attitude that is necessary in language teachers and learners. In conclusion, this study advocates adaptive and reflective teaching as an essential component in the training of future language teachers in globalized contexts.
Keywords: cultural mediation; teacher training; foreign language teaching; teaching methods; teaching practice

Common pitfalls to avoid while using multiobjective optimization in machine learning - Akhter, Junaid; Fährmann, Paul David; Sonntag, Konstantin; Peitz, Sebastian (arXiv)

Zwischen Herrschaft und Utopie . Eine theologische Reflexion über die ambivalente Mensch-Tier-Beziehung - Herdramm, Henrike (Laudato)
Keywords: Tiertheologie; Tierethik; Psalm 104; Mensch-Tier-Beziehung

“I Guess this is Growing Up” Analysis of Pop-Punk’s Regained Popularity and Its Shift From Bands to Personas. - Ruth, Nicolas; Jacke, Christoph (Persona Studies)
This research article examines the transformation of pop-punk from bands to solo artists and how the genre regained popularity due to new popular personalities and the transmedia engagement in social media and with established media. Through a three-pronged approach, this studyadopts phenomenological, theoretical, and empirical perspectives to understand the transition and regained popularity fully. The phenomenological angle delves into the case studies of musicians, revealing key factors behind the shift to solo artists in pop-punk. Theoretical explanations contextualize the phenomenon within broader cultural frameworks, considering industry and transmedia dynamics, audience preferences, and technological advancements. Empirical evidence, including statistical data from socialmedia profiles, quantifies the impact of the shift.This study contributes to a comprehensive understanding of pop-punk's transformation, offering an exploration of its past, present, and future within the ever-evolving music industries and transmedia landscapes
Keywords: Pop-punk; Popular Musical Personas; Solo Artists; SocialMedia; Transmedia; TikTok

Stars, Anti-Stars, Anti-Star-Stars. Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions. - Jacke, Christoph (Persona Studies)
The phenomenon of stars and celebrities in media cultures – and especially in popular music cultures – seems to be omnipresent. At the same time, there is an astounding lack of analysis and research on these media personalities and personas, and international celebrity studies only recently a developing new field. Similarly, these kinds of observations are still very rare especially in German sociology as well as communication, media, culture and popular music studies. In this article, I therefore want to concentrate on the foundations of studying stars and celebrities within the attention economies by undertaking a theoretical transmedia-cultural framing of media personas and suggesting a typology. This ensuing typology of stars, anti-stars, and anti-star stars – especially within popular music cultures – demonstrates how stars and celebrities and their quantities and qualities of success and peer-group specific values coming form programs of (media and music) culture can serve as persona-seismographs of socio-cultural change between tradition and innovation
Keywords: Stars; Celebrities; Popular Music; Transmedia Culture; Personas

Jahrgangsteams zur Kooperation mit Eltern anregen – eine Aufgabe für Fortbildungen? Evaluationsergebnisse zum Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen (BiFoKi) - Grüter, Sandra; Gorges, Julia; Lütje-Klose, Birgit; Neumann, Phillip; Wild, Elke (QfI - Qualifizierung für Inklusion. Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)
Für eine gelingende Umsetzung schulischer Inklusion gilt eine professionelle Weiterbildung der Lehrkräfte und des weiteren Schulpersonals als unverzichtbare Voraussetzung, um eine effektive Teamarbeit sowie die Einbindung von Eltern [i] in Erziehungs- und Bildungsprozesse zu gewährleisten. Im Projekt BiFoKi [ii] (Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen) wurde eine Fortbildungsmaßnahme für inklusive Schulen entwickelt, die sowohl die intrainstitutionelle Kooperation innerhalb der Schule als auch die interinstitutionelle Zusammenarbeit mit den Eltern der Schüler*innen mit und ohne sonderpädagogischen Unterstützungsbedarf adressiert. Die Fortbildung zielt u.a. darauf ab, durch eine im Jahrgangsteam gemeinsam geplante und verantwortete Elternarbeit eine einladende Atmosphäre zu schaffen, Kommunikationswege an diverser werdende Bedarfe der Eltern und der Schüler*innen anzupassen und Eltern stärker in schulische Bildungsprozesse einzubeziehen. Zur Evaluation der Fortbildung wurde eine quasi-experimentelle Studie mit einem Prä-Post-Kontrollgruppendesign realisiert. Längsschnittliche Daten liegen für 55 Lehr- und Fachkräfte vor. Die Ergebnisse der varianzanalytischen Auswertung zeigen, dass sich die Einschätzungen zur Kooperationsbereitschaft der Eltern sowie das selbstberichtete Kooperationsverhalten im Bereich der Erziehungs- und Bildungskooperation in der Interventionsgruppe nach der Teilnahme an der Fortbildung signifikant positiver entwickelt hat als in der Kontrollgruppe. [i] Mit dem Begriff Eltern sind hier alle erziehungs- bzw. sorgeberechtigten Personen gemeint. [ii] Hinweis zur Finanzierung: Das diesem Beitrag zugrunde liegende Vorhaben BiFoKi (Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen) wurde mit Mitteln des Bundesministeriums für Bildung und Forschung unter dem Förderkennzeichen 01NV1732in der Förderlinie „Qualifizierung der pädagogischen Fachkräfte für inklusive Bildung“ gefördert (Projektleitung: Birgit Lütje-Klose, Elke Wild, Julia Gorges und Phillip Neumann).
Keywords: Inklusion; Kooperation; Eltern; Sekundarstufe 1; Evaluation; Integration; Schulentwicklung; Elternkooperation

Religion und Freiheit - Süßmann, Johannes

Pappert, Steffen/Roth, Kersten Sven (Hg.) (2023): Zeitlichkeit in der Textkommunikation. - Markewitz, Friedrich (Zeitschrift für Medienlinguistik)

A mixed‐methods study of the quality of parental support during adolescents' information‐related Internet use as a co‐construction process - Kurock, Ricarda; Teichert, Jeannine; Meister, Dorothee M.; Gerhardts, Lara; Buhl, Heike M.; Bonanati, Sabrina (Journal of Adolescence)
Abstract Introduction In Europe, most Internet searches for school‐related tasks are situated at home, where parents can support adolescents. Although the frequency (quantity) of parental support has already been analyzed, a research gap exists concerning the quality of parental support in adolescents' information‐related Internet use. The quality of parental support in the field of homework involvement is known to be a predictor of adolescents' learning motivation and academic achievement, often discussed with regard to self‐determination theory (SDT) in terms of autonomy support, structure, emotional support, and control. These categories were adapted in this study to analyze parents' support in adolescents' Internet searching activities. Methods Using a mixed‐methods approach, we combined quantitative questionnaires and qualitative observations to analyze joint information‐related Internet uses. Therefore, 243 parent–adolescent dyads were surveyed and six parent–adolescent dyads were observed by videography in 2019/2020 in Germany. The adolescents were 11 years old, on average. Results The parents rated all qualities higher than the adolescents. Emotional support was rated highest by both groups, whereas structure was rated lowest. Adolescents' and parents' view on parental support differ. The qualitative study revealed parents' often interfering behavior, whereas emotional support was low. Further, the active role of adolescents was highlighted in both quantitative and qualitative data. Conclusions By combining quantitative and qualitative approaches, we demonstrated a fruitful application of SDT in analyzing the quality of parental support during adolescents' Internet searches at home and shed light on the co‐construction of joint Internet searches.
Keywords: Psychiatry and Mental health; Developmental and Educational Psychology; Social Psychology; Pediatrics; Perinatology and Child Health

State of Knowledge Managementamong German firefighters - Schultz, Andreas Maximilian; Dotzki, Fabian; Mozgova, Iryna (Proceedings of the 21st ISCRAM Conference)

Modeling the Quality of Dialogical Explanations - Alshomary, Milad; Lange, Felix; Booshehri, Meisam; Sengupta, Meghdut; Cimiano, Philipp; Wachsmuth, Henning (Proceedings of the 2024 Joint International Conference on Computational Linguistics, Language Resources and Evaluation (LREC-COLING 2024))
Explanations are pervasive in our lives. Mostly, they occur in dialogical form where an explainer discusses a concept or phenomenon of interest with an explainee. Leaving the explainee with a clear understanding is not straightforward due to the knowledge gap between the two participants. Previous research looked at the interaction of explanation moves, dialogue acts, and topics in successful dialogues with expert explainers. However, daily-life explanations often fail, raising the question of what makes a dialogue successful. In this work, we study explanation dialogues in terms of the interactions between the explainer and explainee and how they correlate with the quality of explanations in terms of a successful understanding on the explainee’s side. In particular, we first construct a corpus of 399 dialogues from the Reddit forum Explain Like I am Five and annotate it for interaction flows and explanation quality. We then analyze the interaction flows, comparing them to those appearing in expert dialogues. Finally, we encode the interaction flows using two language models that can handle long inputs, and we provide empirical evidence for the effectiveness boost gained through the encoding in predicting the success of explanation dialogues.
Keywords: Corpus; Explanation; Discourse Annotation; Explainability

Natural near field coupled leaky-mode resonant anti-reflection structures: the setae of Cataglyphis bombycina - Schwind, Bertram; Wu, Xia; Tiemann, Michael; Fabritius, Helge-Otto (Frontiers in Physics)
Leaky mode resonances of the setae of Cataglyphis bombycina are found to enhance the thermal emission of the animals by near field coupling to the chitinous exoskeleton. This is remarkable, as the setae are also an adaption to enhance the reflectivity in the visible wavelength range. Both effects are dependent on morphology, dimensions and spatial arrangement. These parameters were experimentally characterized and simulated by finite difference time domain simulations to elucidate the optical impact of the setae in the mid infrared range and the contribution of leaky mode resonances. This mode of action and the setae’s optical properties in the visible range explain evolutionary strains that led to the actual morphology and size of the setae.

Beyond One-Shot Explanations: A Systematic Literature Review of Dialogue-Based XAI Approaches - Mindlin, Dimitry; Beer, Fabian; Sieger, Leonie Nora; Heindorf, Stefan; Cimiano, Philipp; Esposito, Elena; Ngonga-Ngomo, Axel-Cyrille
In the last decade, there has been increasing interest in allowing users to understand how the predictions of machine-learned models come about, thus increasing transparency and empowering users to understand and potentially contest those decisions.Dialogue-based approaches, in contrast to traditional one-shot eXplainable Artificial Intelligence (XAI) methods, facilitate interactive, in-depth exploration through multi-turn dialogues, simulating expert conversations. This paper reviews the current state of dialogue-based XAI, presenting a systematic review of 1,339 publications, narrowed down to 14 based on inclusion criteria. We explore theoretical foundations of the systems, propose key dimensions along which different solutions to dialogue-based XAI differ, and identify key use cases, target audiences, system components, and the types of supported queries and responses. Furthermore, we investigate the current paradigms by which systems are evaluated and highlight their key limitations. Key findings include identifying the main use cases, objectives, and audiences targeted by dialogue-based XAI methods, and summarize the main types of questions and information needs. Beyond discussing avenues for future work, we present a meta-architecture for these systems from existing literature and outlined prevalent theoretical frameworks.

Universal Knowledge Graph Embeddings - KOUAGOU, N'Dah Jean; Demir, Caglar; Zahera, Hamada Mohamed Abdelsamee; Wilke, Adrian; Heindorf, Stefan; Li, Jiayi; Ngonga Ngomo, Axel-Cyrille (Companion Proceedings of the ACM on Web Conference 2024)

Utilizing Description Logics for Global Explanations of Heterogeneous Graph Neural Networks - Köhler, Dominik; Heindorf, Stefan (arXiv:2405.12654)
Graph Neural Networks (GNNs) are effective for node classification in graph-structured data, but they lack explainability, especially at the global level. Current research mainly utilizes subgraphs of the input as local explanations or generates new graphs as global explanations. However, these graph-based methods are limited in their ability to explain classes with multiple sufficient explanations. To provide more expressive explanations, we propose utilizing class expressions (CEs) from the field of description logic (DL). Our approach explains heterogeneous graphs with different types of nodes using CEs in the EL description logic. To identify the best explanation among multiple candidate explanations, we employ and compare two different scoring functions: (1) For a given CE, we construct multiple graphs, have the GNN make a prediction for each graph, and aggregate the predicted scores. (2) We score the CE in terms of fidelity, i.e., we compare the predictions of the GNN to the predictions by the CE on a separate validation set. Instead of subgraph-based explanations, we offer CE-based explanations.

Causal Question Answering with Reinforcement Learning - Blübaum, Lukas; Heindorf, Stefan (The World Wide Web Conference (WWW))

Histories of Tax Evasion, Avoidance and Resistance - Schönhärl, Korinna; Hürlimann, Gisela; Rohde, Dorothea
Tax evasion, tax avoidance and tax resistance are widespread phenomena in political, economic, social and fiscal history from antiquity through medieval, early modern and modern times. Histories of Tax Evasion, Avoidance and Resistance shows how different groups and individuals around the globe have succeeded or failed in not paying their due taxes, whether in kind or in cash, on their properties or on their crops. It analyses how, throughout history, wealthy and poor taxpayers have tried to avoid or reduce their tax burden by negotiating with tax authorities, through practices of legal or illegal tax evasion, by filing lawsuits, seeking armed resistance or by migration, and how state authorities have dealt with such acts of claim making, defiance, open resistance or elusion. It fills an important research gap in tax history, addressing questions of tax morale and fairness, and how social and political inequality was negotiated through taxation. It gives rich insights into the development of citizen-state relationships throughout the course of history. The book comprises case studies from Ancient Athens, Roman Egypt, Medieval Europe, Early Modern Mexico, the Ottoman Empire, Nigeria under British colonial rule, the United Kingdom of the early 20th century, Greece during the Second World War, as well as West Germany, Switzerland, Sweden and the United States in the 20th century, including transnational entanglements in the world of late-modern offshore finance and taxation. The authors are experts in fiscal, economic, financial, legal, social and/or cultural history. The book is intended for students, researchers and scholars of economic and financial history, social and world history and political economy. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Share Alike 4.0 license.
Keywords: Tax History; Financial History

The Ability and Intention of Not Paying Taxes in History. Some Introductory Observations - Schönhärl, Korinna; Hürlimann, Gisela; Rohde, Dorothea (Histories of Tax Evasion, Avoidance and Resistance)
Jean Bodin's list on how the absolutist monarchical state could raise its revenue ranked taxation only in seventh place. From a modern legal perspective, taxes are compulsory transfers of resources that households and enterprises pay to one or several government bodies without receiving an individual, specific benefit in return. Historians have dealt with not paying taxes in various contexts, such as analysing tax resistance and tax resistance movements in history. Tax law is best understood as an outcome of long-term, often conflictual, negotiations and as an expression of specific political mentalities and ideologies. As a consequence, tax law and sometimes even the tax juridical system have a strongly politicised character. Loopholes in tax legislation that enable or facilitate avoidance or evasion can thus be regarded as a result of the interest-driven politics of parliamentary majorities, as the success of concerted lobby pressure.

How to Create a Taxpaying Spirit. A Transnational Examination of an US American and a Western German Tax Education Film in and after World War II - Schönhärl, Korinna (Histories of Tax Evasion, Avoidance and Resistance)
As a case study, this chapter examines two tax education films that were produced 11 years apart in the USA and Western Germany during and after World War II: “The New Spirit” and “Putzke wants to know”. In contrast to America's most popular cartoon character 11 years earlier, Erwin Putzke is in a terrible mood at the beginning of the short film “Putzke wants to know”. The family father and electrician with a workshop of his own is annoyed and upset by the duty of filling in his tax return, grumbling at his wife and daughter and even at their budgie. The film's tax morale message is conveyed to its audience against the backdrop of a sober post-war reality characterised by allied occupation and the Allies' say in West German tax policies during a period of laborious economic build-up after a lost war.